2019
DOI: 10.2478/intox-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the clinical consequences of butyrfentanyl and corresponding analogues

Abstract: Butyrfentanyl and its analogues are being increasingly used throughout the United States and Europe. Currently, lethal cases are emerging across the United States, England, and Europe without any end in sight. We therefore performed a systematic review of existing case reports on the literature of butyrfentanyl and similar analogs. We searched PubMed and Embase for articles (up until September 2018) using terms such as “butyrfentanyl” or “butyrylfentanyl.” In total, our search found 271 articles and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Butyrfentanyl is another fentanyl analog that appeared in the illicit market in 2015, causing a growing number of deaths related to its use. As a result, it was scheduled by the DEA in 2017 19 .…”
Section: Butyrfentanylmentioning
confidence: 99%
“…Butyrfentanyl is another fentanyl analog that appeared in the illicit market in 2015, causing a growing number of deaths related to its use. As a result, it was scheduled by the DEA in 2017 19 .…”
Section: Butyrfentanylmentioning
confidence: 99%
“…Another NSO recognized as a schedule I drug by the DEA is butyrfentanyl (BF), an analog of fentanyl. A recent systematic review of 10 articles covering a total of 33 cases, 20 of which postmortem, revealed a trend of significant pulmonary and cardiovascular damage among patients who used BF or a similar analog [4]. Of patients that survived, many required ICU stays, with some patients needing ventilator support due to pulmonary aspiration or intubation in the course of treatment.…”
Section: Editorialmentioning
confidence: 99%
“…Illicit drug manufacturers modify the structural backbone of fentanyl to generate fentanyl analogs to circumvent drug detection and regulation. Multiple fentanyl analogs have been detected in drug products and biological specimens over the past decade and their diversity continues to evolve [2] , [3] , [4] , [5] , [6] , [7] , [8] . The current prevalence of fentanyl analogs and synthetic opioids in patients seeking medical care is unknown as specific identification methods have not been routinely used in clinical settings.…”
Section: Introductionmentioning
confidence: 99%